Effekter av två olika hösilagefoderstater på tarmfloran och träcksammansättningen hos häst och gris - Ringmark, Sara (2008)
The aim of this study was to investigate if the botanical composition of haylage affects pH, dry matter content and microbial composition of the faeces in horse and pig and ileal environment in pigs. Two separate studies were conducted where pigs and horses were fed two diets containing haylages with different botanical composition. The first haylage was from a tilled land dominated by timothy and meadow fescue and the other haylage came from a meadowland with a large inclusion of dandelion, 25 % and common couch. The dry matter content (70.8 % and 73.0 % respectively) and the pH-value (5.7) were similar in both feeds.